A Systematic Review and Meta-Analysis of Interventions for Actinic Keratosis from Post-Marketing Surveillance Trials - Steeb, Theresa; Wessely, Anja; Harla, Matthias; Heppt, Franz; Koch, Elias; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2020)
Multiple interventions are available for the treatment of actinic keratosis (AK) showing high efficacy in pivotal trials. However, data from post-marketing surveillance studies have received little attention until now. Here, we systematically investigate interventions for AK from post-marketing surveillance trials as a proxy for real-world efficacy and tolerability. A systematic literature search was conducted in Medline, Embase, and CENTRAL. Pertinent trial registers were hand-searched until 25 March 2020. Results were pooled using a random-effects model to calculate pooled proportions and relative risks (RR) or were described qualitatively. Eleven records with a total sample size ofn= 4109 were included. Three of the studies had an active-controlled design, while seven were single-armed. Participant complete clearance ranged from 23.1% for diclofenac sodium 3% gel to 88.9% for ingenol mebutate 0.05% gel. The lesion-specific clearance rate for photodynamic therapy (PDT) was 74% (95% confidence interval (CI) 56-87%). The recurrence rate was significantly higher for diclofenac sodium 3% in comparison to imiquimod 5% cream (RR 1.10, 95% CI 1.02-1.1.8) and ranged from 10.6% for ingenol mebutate 0.015% gel to 23.5% for PDT. Few patients discontinued the trials due to adverse events. The results from the majority of the post-marketing surveillance studies deviated from those of pivotal trials.
CRIS-Team WoS Importer:2020-08-21